Productive performance of Dorper sheep - Cloete, S.W.P.; Snyman, M.A.; Herselman, M.J. (Elsevier, 2000)
The Dorper is a hardy South African composite breed, derived from a cross between the Black-headed Persian and the Dorset Horn. Dorpers are regarded as early-maturing, and ewes lambed at an age of 1 year in one study. Age at first lambing was higher in other literature sources cited. The fertility of Dorper ewes was approximately 0.90 ewes that lambed per ewe mated, with a litter size ranging from 1.45 to 1.60. The gestation length of Dorper ewes was approximately 147 days, while they were reported to start cycling as soon as 52 days after parturition. The pre-weaning survival of Dorper lambs was cited at approximately 0.90. Overall reproduction rate of Dorpers ranged from 0.99 to 1.40 lambs weaned per ewe mated, while it exceeded 1.40 lambs weaned per ewe mated per annum under accelerated mating conditions. Dorper lambs gained from 0.24 to 0.28 kg per day under vastly different environmental conditions. When weaned early at 2–3 months of age, post-weaning gains in excess of 0.18–0.20 kg per day were recorded. At slaughter, Dorper lambs had dressing percentages of approximately 50%. Two divergent genotypes in the breed (with a hairy or a woolly fleece cover) were evaluated under natural pasture conditions. No conclusive advantage in favour of either genotype could be demonstrated as far as productive traits were concerned. It was concluded that the breed adapts well to a wide variety of environmental conditions. In view of the scarcity of estimates of genetic parameters for the breed, the maintenance and expansion of datasets suitable for this purpose should receive high priority.